Artificial Intelligence and Digital Literacy in Education: a systematic bibliometric review - Xu, Bin; Teh, Sin Yin; Saha, Sajal; Zhang, Naiheng (Bibliotecas. Anales de investigación, 2025)
Objective: Artificial intelligence (AI) and digital literacy are transforming education by reshaping teaching practices, learning processes, educational quality, and skills development. This study aims to systematically present the developmental landscape of this field. Methodology: A bibliometric approach is adopted to review and analyze 183 articles published in the Web of Science Core Collection between 2017 and 2025. This study employs VOSviewer and Scimago Graphica to examine publication patterns, influential research, collaboration networks, and thematic clusters. Results and Discussion: The findings indicate that since 2023, both the number of publications and citations have risen sharply, suggesting growing academic attention and increasing scholarly impact. Education-related disciplines remain dominant, while contributions from computer science and other cross-disciplinary fields highlight the interdisciplinary nature of the research. Highly cited papers are mainly focused on applications in higher education, teacher training, healthcare, and agriculture. At the international level, Europe has established extensive collaboration networks. China ranks first in the number of publications, whereas Germany demonstrates strong citation impact. The keyword co-occurrence analysis identifies six clusters, covering technological, pedagogical, ethical, and institutional aspects. The overlay visualization further reveals temporal changes, showing a shift from early research focused on technology and pedagogy to more recent explorations of ethics, governance, and trust. Conclusions: Overall, the results confirm that research on AI and digital literacy has accelerated since 2023, with increasing interdisciplinarity and evolving research priorities. Contribution: This study outlines the prospects of research on AI and digital literacy and provides important insights into current trends and future directions.